Discovery of two new weevil species of Pholicodes Schoenherr, 1826 (Coleoptera: Curculionidae: Entiminae) from eastern Turkey - Gültekin,Levent; Gültekin,Neslihan (PeerJ, 2025)
Weevils are beetles belonging to the superfamily Curculionoidea, known for their elongated snouts commonly named as rostrum. This superfamily is the most species-rich group in Insecta as well as Animalia kingdom, all they are considered phytophagous. The broad nosed weevil genus of Pholicodes Schoenherr, 1826 is solely Palearctic distribution with forty species. In this study, two new species Pholicodes artemisiae sp. nov. and Pholicodes hakkaricus sp. nov. are described from eastern Turkey. Morphological taxonomic characters are digitally illustrated. The new species Ph. artemisiae sp. nov. is associated with Artemisia plant and Ph. hakkaricus sp. nov. collected on Inula helenium L. in the habitat mountain slopes.
Keywords: Pholicodes; New species; Curculionidae; Anatolia; Turkey